2016
DOI: 10.1093/jcr/ucw033
|View full text |Cite
|
Sign up to set email alerts
|

Slowing Down in the Good Old Days: The Effect of Nostalgia on Consumer Patience

Abstract: Nostalgia, which is induced by reminiscing about a positive past experience, can counteract loneliness and promote prosocial behavior. However, the process of recalling and thinking about a nostalgic experience can have quite different effects. Because nostalgic experiences rarely reoccur, people are motivated to savor them by prolonging the time they reminisce about them. The tendency to savor these experiences generalizes to situations that participants encounter later, thus increasing consumer patience. For… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
95
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 82 publications
(118 citation statements)
references
References 71 publications
0
95
0
3
Order By: Relevance
“…Specifically, previous studies have demonstrated that when feeling nostalgic, consumers tend to express more positive attitudes toward the advertising (Muehling, Sprott, & Sultan, 2014), pay more for products because of weakened desire for money (Lasaleta, Sedikides, & Vohs, 2014), and show more patience while waiting in the restaurant (Huang, Huang, & Wyer, 2016). However, extant research mainly focuses on how nostalgia affects one's own choice.…”
mentioning
confidence: 99%
“…Specifically, previous studies have demonstrated that when feeling nostalgic, consumers tend to express more positive attitudes toward the advertising (Muehling, Sprott, & Sultan, 2014), pay more for products because of weakened desire for money (Lasaleta, Sedikides, & Vohs, 2014), and show more patience while waiting in the restaurant (Huang, Huang, & Wyer, 2016). However, extant research mainly focuses on how nostalgia affects one's own choice.…”
mentioning
confidence: 99%
“…A less obvious mindset was identified by Huang, Huang, and Wyer (). Ruminating about a positive past experience that was unlikely to reoccur is likely to elicit a desire to “relive” the experience and to prolong one's reminiscence of it.…”
Section: The Impact Of Behavioral Mindsets On Judgments and Decisionsmentioning
confidence: 97%
“…Majority of nostalgic memories include elements of love, pride, and happiness (Davis, 1979;Holak and Havlena, 1992;Wildschut et al, 2006). Nostalgia can serve a variety of functions (Huang et al, 2016). It can encourage feelings of being loved and protected (Juhl et al, 2010) and thus can counteract feelings of loneliness (Wildschut et al, 2006;Zhou et al, 2008).…”
Section: Perceived Qualitymentioning
confidence: 99%